Funcionalidade dos utentes internados no domicílio em equipas de cuidados continuados integrados, ECCI : intervenção do enfermeiro especialista em enfermagem de reabilitação - Marvanejo, Duarte José Draque (2016)
Abstract Background: The increase in the number of old and very old people and the need to take care of the patient at home potentiated new necessities in the context of the organization of primary healthcare. Consequently, emerged the Integrated Continuing Care Teams (ECCI), included in the Integrated Continuing Care National Network (RNCCI), which aims to provide care in a perspective of rehabilitation and/or satisfaction of needs of the dependent person, as well as the participation and accountability of the family in the provision of home care. Goals: Identify and compare the functionality presented by the patients hospitalized in the ECCI (with or without Rehabilitation Nurses) and analyze associations between sociodemographic, clinical and context variables and patients’ functionality. Methods: This is a non-experimental descriptive study, with cross-sectional comparative and correlational nature, included in the quantitative methodologies paradigm. It was performed in a non-probabilistic sample for convenience, consisting of 60 patients (33 in the control group without home visit of the Rehabilitation Nurse Specialist and 27 in the experimental group with home visit of the Rehabilitation Nurse Specialist) hospitalized in the ECCI locations between January 1st of 2015 and August 31st of 2016. The data collection instrument integrates 4 characterization sections: sociodemographic, clinical, context and the National Functionality Table. Results: It was found that 56.7% of the global sample had very limited functionality, 26.7% had absent functionality, 15% had reduced functionality and no patients presented full functionality. The group analysis shows that the functionality levels in the experimental group (OM=29,94) were higher than the ones observed in the control group (OM=30,95). We also verified that in the experimental group, the urban residential area patients (p=0.05) and those who had 3 weekly home visits of the EEER (p=0.046) show higher functionality. In the control group, patients who do not know how to read or write (p=0.004), who were hospitalized in the last 6 months in the RNCCI (p=0.011) and who had an Informal Caregiver (p=0.044) present reduced functionality. Conclusion: The evidence found in this study point to the fact that the functionality of these patients is greatly reduced and, therefore, the challenge presented to the EEER included in ECCI, is to take care of the patient and his caregiver in order to maintain functionality. As a result, the continuation of healthcare providing at home, continuously and in an integrated perspective, presents itself with a critical role that allows the establishment of a structured rehabilitation program focused on the patient and his family. This is the paradigm that currently emerges in primary healthcare and applying it is a duty not only of professionals, but also institutions.